Lamotrigine and aseptic meningitis - Simms, Kelley M; Kortepeter, Cindy; Avigan, Mark (Neurology, 2012)
The purpose of this case series is to characterize a recently identified association of the antiepileptic drug (AED) lamotrigine with aseptic meningitis based on cases reported to the Food and Drug Administration (FDA)'s Adverse Event Reporting System (AERS) database. We performed a data mining analysis of 9 AEDs from the FDA's AERS database. We applied the multi-item gamma Poisson shrinker (MGPS) algorithm to the entire AERS database through November 2, 2009, to generate empirical Bayes geometric mean (EBGM) values with corresponding confidence intervals for 9 AEDs and the adverse event code "meningitis aseptic." The AERS database was also searched for postmarketing reports of aseptic meningitis associated with lamotrigine and a detailed review of each case was performed. Forty AERS cases were identified in this review. Findings from the AERS reports revealed CSF profiles with features of both bacterial as well as viral meningitis. Fifteen cases documented a positive rechallenge; the median time to onset of symptoms upon rechallenge was only 60 minutes. Data mining analysis of several anticonvulsants resulted in disproportionate reporting solely for lamotrigine. There appears to be an association between lamotrigine use and aseptic meningitis. It is notable that nearly 40% of cases in this case series reported a positive rechallenge. Lamotrigine-associated aseptic meningitis should be considered in the differential diagnosis of culture-negative meningitis. This case series highlights the need for continued pharmacovigilance and the importance of systematic monitoring of patients treated with antiepileptic medications.